Role of PI3K/Akt and MEK/ERK Signalling in cAMP/Epac-Mediated Endothelial Barrier Stabilisation - Gündüz, Dursun; Troidl, Christian; Tanislav, Christian; Rohrbach, Susanne; Hamm, Christian; Aslam, Muhammad (Frontiers in Physiology, 2019)
Background and Aims Activation of the cAMP/Epac signalling stabilises endothelial barrier function. Moreover, its activation is accompanied by an activation of PI3K/Akt and MEK/ERK signalling in diverse cell types but their impact on endothelial barrier function is largely unknown. Here the role of PI3K/Akt and MEK/ERK signalling in cAMP/Epac-mediated endothelial barrier stabilisation was analysed. Methods Endothelial barrier function was analysed in cultured human umbilical vein endothelial cells (HUVECs) by measuring flux of albumin. A modified cAMP analogue 8-pCPT-2′-O-Me-cAMP (Epac agonist) was used to specifically activate cAMP/Epac signalling. Results Epac agonist reduces the basal and attenuates thrombin-induced endothelial hyperpermeability accompanied by an activation of PI3K/Akt and MEK/ERK signalling. The qPCR data demonstrate HUVECs express PI3Kα, PI3Kβ, and PI3Kγ but not PI3Kδ isoforms. The western blot data demonstrate Epac agonist activates PI3Kα and PI3Kβ isoforms. Inhibition of MEK/ERK but not PI3K/Akt pathway potentiates the endothelial barrier protective effects of cAMP/Epac signalling. Inhibition of MEK/ERK signalling in the presence of Epac agonist induces a reorganisation of actin cytoskeleton to the cell periphery, enhanced VE-cadherin localisation at cell-cell junctions, and dephosphorylation of myosin light chains (MLC) but not inhibition of RhoA/Rock signalling. Moreover, Epac agonist promotes endothelial cell (EC) survival via reduction in activities of pro-apoptotic caspases in a PI3K/Akt and MEK/ERK signalling-dependent manner. Conclusion Our data demonstrate that the Epac agonist simultaneously activates diverse signalling pathways in ECs, which may have differential effects on endothelial barrier function. It activates PI3K/Akt and MEK/ERK signalling which mainly govern its pro-survival effects on ECs. Inhibition of MEK/ERK but not PI3K/Akt signalling enhances barrier stabilising and barrier protective effects of cAMP/Epac activation. Chemical Compounds Used In This Study 8-pCPT-2′-O-Me-cAMP (PubChem CID: 9913268); Akt inhibitor VIII (PubChem CID: 10196499); AS-252424 (PubChem CID: 11630874); IC-87114 (PubChem CID: 9908783); PD 98059 (PubChem CID: 4713); PIK-75 (PubChem CID: 10275789); TGX-221 (PubChem CID: 9907093); Thrombin (PubChem CID: 90470996); U0126 (PubChem CID: 3006531); Wortmannin (PubChem CID: 312145).